Introducing the Human Library Concept as a Tool to Mitigate Work and Household Stress among Working Mothers at UENR - Attafuah, Harriet Fosua; Amanquah, Pearl Owusua (International Journal of Knowledge Content Development & Technology, 2025)
Most women experience some form of stress at some point in their lives. However, these stress levels are exacerbated when the woman becomes both a mother and a career woman. The study explored how the human library concept can be used as a tool to mitigate work and household stress among working mothers at the University of Energy and Natural Resources. The study adopted the qualitative research approach. 15 out of 92 mothers of the Senior Staff of Universities of Ghana (SSAUoG) at UENR were purposively sampled. The findings revealed that majority of the working mothers feel stressed in combining work roles and domestic roles. To help mitigate the stress levels, the mothers saw a solution in interacting with each other and sharing their knowledge and experiences which is what the human library stands for. Hence, employers who expect mothers to deliver excellently at their assigned duties must employ the human library concept as a tool to mitigate stress among its working mothers.